2016
DOI: 10.1101/075036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hand2 Inhibits Kidney Specification While Promoting Vein Formation Within the Posterior Mesoderm

Abstract: Proper organogenesis depends upon defining the precise dimensions of organ progenitor territories. Kidney progenitors originate within the intermediate mesoderm (IM), but the pathways that set the boundaries of the IM are poorly understood. Here, we show that the bHLH transcription factor Hand2 limits the size of the embryonic kidney by restricting IM dimensions. The IM is expanded in zebrafish hand2 mutants and is diminished when hand2 is overexpressed. Within the posterior mesoderm, hand2 is expressed latera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 61 publications
6
27
0
Order By: Relevance
“…3F). Extending previous observations (Gays et al, 2017;Mao et al, 2015;Perens et al, 2016;Yin et al, 2010), these data suggest that hand2:EGFP reporter expression at 3 dpf in zebrafish delineates the visceral and parietal peritoneal membranes.…”
Section: Hand2 Expression Identifies Mesothelial Progenitorssupporting
confidence: 88%
“…3F). Extending previous observations (Gays et al, 2017;Mao et al, 2015;Perens et al, 2016;Yin et al, 2010), these data suggest that hand2:EGFP reporter expression at 3 dpf in zebrafish delineates the visceral and parietal peritoneal membranes.…”
Section: Hand2 Expression Identifies Mesothelial Progenitorssupporting
confidence: 88%
“…The strong proximal deficiencies observed in osr1 mutants were reminiscent of the pronephron phenotypes previously shown to result from overexpression of hand2 (Perens et al, 2016).…”
Section: Mutation Of Osr1 Has Graded Effects Along the Proximal-distasupporting
confidence: 55%
“…Previously we found that hand2 constrains the size of the pronephron by repressing IM formation (Perens et al, 2016). Considering the genetic interaction between hand2 and osr1 during pronephron development, we investigated whether osr1 also regulates the extent of initial IM formation.…”
Section: Osr1 Is Required To Generate the Full Complement Of Intermedmentioning
confidence: 97%
See 1 more Smart Citation
“…We find that while pax2.1:EGFP in early somitogenesis marks midbrain-hindbrain precursor cells of ectodermal origin, the likewise pax2.1:EGFP-expressing PLPM-derived pronephric epithelial precursors (Picker et al, 2002) also express drl:mCherry ( Fig 1K). Moreover, hand2:EGFP expression, which demarcates the lateral-most PLPM domain plus parts of the ALPM-derived heart field and pectoral fin precursors (Perens et al, 2016;Yelon et al, 2000), was also fully situated within the pan-LPM expression domain of drl:mCherry ( Fig 1L). Taken together, these data provide a continuous view of the emerging LPM stripes from gastrulation in zebrafish and document that the LPM emerges around the entire circumference of the zebrafish embryo ( Fig 1M).…”
Section: The Lpm Emerges As a Dedicated Mesendoderm Populationmentioning
confidence: 92%